(untitled) (Medical Forum Monthly, 2026)
Objective: To evaluate the histopathological alterations in renal tissue following chromium exposure, in different doses with particular emphasis on kidney injury molecule -1as a biomarker of renal damage. Study Design: experimental studyPlace and Duration of Study: This study was conducted at the College of Medicine, Al-Nahrain University,Baghdad, Iraq from 1st September 2025 to 30th November 2025. Methods: This experimental group was exposed to different doses of chromium and compared with the control group. Histological analysis was performed and Kim-1 was assessed to evaluate tubular injury. Results: Chromium exposure resulted in noticeable histological changes, treated groups showed enlargement of the urinary space and degenerative changes in proximal convoluted tubules. In addition, kim-1 expression was markedly elevated indicating early tubular injury based on dose dependent effect. Conclusion: Chromium induces significant dose-dependent renal damage at both structural and cellular levels and the nephrotoxic potential of Chromium and support the utility of kim-1 as a sensitive biomarker for early detection of kidney injury.